2008
DOI: 10.1093/rheumatology/ken086
|View full text |Cite
|
Sign up to set email alerts
|

Role of hypoxia-inducible factor-1  in hypoxia-induced expressions of IL-8, MMP-1 and MMP-3 in rheumatoid fibroblast-like synoviocytes

Abstract: Hypoxia-induced MMP-3 expression is exclusively regulated by HIF-1alpha, and hypoxia-induced MMP-1 or IL-8 expression appears to have salvage pathways other than the HIF-1alpha pathway. Together, these data provide new insight regarding the mechanism by which hypoxia participates in joint inflammation and destruction in RA.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
69
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 96 publications
(71 citation statements)
references
References 27 publications
1
69
1
Order By: Relevance
“…The feasibility of this approach was demonstrated using H 2 O 2 -specific antioxidants, showing they can dramatically reduce SA IL-1␣ expression and ultimately prevent expression of the downstream SASP factors IL-6 and IL-8. Interestingly, IL-8 expression is not sensitive to low O 2 exposure, which is likely explained by the fact that IL-8 expression can be regulated by hypoxia-inducible factor-1␣ (37)(38)(39), which is stabilized in the 0.1-4% O 2 range (40). Although antioxidants limit the expression of IL-1␣, they may also prevent the Ca 2ϩ -dependent processing of this factor.…”
Section: Discussionmentioning
confidence: 99%
“…The feasibility of this approach was demonstrated using H 2 O 2 -specific antioxidants, showing they can dramatically reduce SA IL-1␣ expression and ultimately prevent expression of the downstream SASP factors IL-6 and IL-8. Interestingly, IL-8 expression is not sensitive to low O 2 exposure, which is likely explained by the fact that IL-8 expression can be regulated by hypoxia-inducible factor-1␣ (37)(38)(39), which is stabilized in the 0.1-4% O 2 range (40). Although antioxidants limit the expression of IL-1␣, they may also prevent the Ca 2ϩ -dependent processing of this factor.…”
Section: Discussionmentioning
confidence: 99%
“…F2 could inhibit the hypoxia-simulated tumor angiogenesis and cell invasion in vitro in a HIF-1α-dependent manner, and MMP-2 may be the key protein participating in the inhibitory effect of F2 on cell invasion because it could be involved in the breakdown of the extracellular matrix (31). However, there are other proteins participating in the hypoxia-induced tumor invasion, such as CXC chemokine receptor 4 (CXCR4) and interleukin-8 (IL-8) (38,39). Accordingly, additional studies are underway to identify the associated genes that are directly or indirectly involved in the inhibitory effect of F2 on tumor cell invasion in response to hypoxia and/or HIF-1α overexpression.…”
Section: Discussionmentioning
confidence: 99%
“…Previous reports indicate that NF-B, p38, and JNK pathways are involved in MMP1 expression by cytokine stimulation in fibroblast or chondrocytes (10,11). It was also reported that induction of MMP1 is mediated by HIF-1 during hypoxia in fibroblasts (12,13) or by HIF-2 in chondrocytes upon IL-1␤ stimulation (14). Although HIF is a key regulator of the hypoxic response, it remains unclear if MMP1 is induced by these factors during prolonged hypoxia or if any other factor(s) is involved in MMP1 induction.…”
mentioning
confidence: 99%